A Theoretical Analysis Upon the Environmental Health and Justice Issue: A Case Study for a Comparison Between G20s Unitary and Federal Members - AKIN, Soner; Gül, Zehra; Yıldırım, Uğur (International Journal of Sustainable Development & World Policy, 2016)
Environmental health and its ties with carbon emission policies have gradually become a hot topic in environmental agenda of nations. In this study, we discuss the issue as environmental health and justice issue in different types of governmental approaches in public management. In this respect, the comparative position of federal and unitary governments were paid attention and the status about sustainable development prospects were analyzed together through looking at the CO2 emission rates and the workers who are under the effect of those policies, benefiting from disability adjusted life years (DALY) statistics.